On Full k-ideals of a Ternary Semiring - Wani, Swapnil; Pawar, Kishor (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, we generalize the concept of the full -ideals of a semiring to ternary semiring and prove that the set of zeroids annihilator of a right ternary semimodule, and the Jacobson radical of a ternary semiring are all full -ideals of. Also we prove that the set of all full -ideals of a ternary semiring is a complete lattice which is also modular.